Evaluation Of Sports And Health Physical Education Lessons For Smp During The Covid 19 Period In Medan City - Harahap, Sutan Baharsyah; Suharjana (Pena Cendekia Insani, 2022)
The purpose of this study is to assess the implementation of learning during Covid19 at SMP Negeri Medan City in terms of Context, Input, Process, and Product. The CIPP model will be used in this study as an assessment model. The subjects of this study are Medan City State Junior High School principals, PJOK teachers, and student participants. Purposive sampling was used, with information on 44 principals, 44 PJOK teachers, and 88 students. Methods for gathering information that include observation, interviews, questionnaires, and documentation. The quantitative descriptive analysis method was used in this study to analyze information. (1) Overall, the results of the evaluation of the implementation of PJOK learning at the Medan City State Middle School during the Covid-19 period were in the good category. (2) The context of the evaluation of the implementation of PJOK learning during the Covid-19 period at the Medan City State Junior High School, which received a questionnaire score of 3.37, as evidenced by the preparation of the PJOK learning curriculum in forty-four SMPNs in the city of Medan. (3) Input on the evaluation of the current PJOK learning implementation of the Covid-19 pandemic at the Medan City Public Middle School yielded positive results. Based on the study's findings, the researchers concluded that the evaluation of PJOK learning inputs at Medan City State Junior High School during the Covid 19 pandemic was very good, with a total score of 3.53. (4) The process of evaluating the implementation of PJOK learning at Medan City State Middle School during the Covid-19 pandemic was rated as good. Based on research data, the indicators of learning activities that the evaluation of the process in the implementation of PJOK learning at the Medan City State Middle School during the Covid 19 period had a good predictor with 3.12 points. (5) The results of the product evaluation of the implementation of PJOK learning during the Covid 19 period in Medan City were good, with 3.26 points.